I DRANK BECAUSE I WANTED TO DEAL WITH THE FRUSTRATION”: EXPLAINING ALCOHOL CONSUMPTION DURING PREGNANCY IN A LOW-RESOURCE SETTING – WOMEN’S, PARTNERS AND FAMILY MEMBERS’ NARRATIVES - Macleod, Catriona Ida; Matebese, Sibongile; Tsetse, Nontozamo (Social Work/Maatskaplike Werk, 2020)
Understanding the explanatory narratives that women, partners and family members provide for consuming alcohol during pregnancy is essential in interventions. This paper reports on the stories of 25 participants in a low-resource area. Explanations included lack of partner support (not providing financially, being unfaithful, denying paternity), stress (HIV diagnosis, unwanted pregnancy, poverty), trauma (rape, death and crime), and a drinking culture (unregulated taverns, availability of liquor, peer pressure). Interventions should work with the gender norms; provide services or referrals for trauma; provide non-judgmental counselling; and target drinking in general in the community so as to reduce drinking culture.